Intraspecific Variation in Wood Anatomical, Hydraulic, and Foliar Traits in Ten European Beech Provenances Differing in Growth Yield - Hajek, Peter; Kurjak, Daniel; von Wühlisch, Georg; Delzon, Sylvain; Schuldt, Bernhard (Frontiers in Plant Science, 2016)
In angiosperms, many studies have described the inter-specific variability of hydraulic-related traits and little is known at the intra-specific level. This information is however mandatory to assess the adaptive capacities of tree populations in the context of increasing drought frequency and severity. Ten 20-year old European beech (Fagus sylvatica L.) provenances representing the entire distribution range throughout Europe and differing significantly in aboveground biomass increment (ABI) by a factor of up to four were investigated for branch wood anatomical, hydraulic, and foliar traits in a provenance trial located in Northern Europe. We quantified to which extend xylem hydraulic and leaf traits are under genetic control and tested whether the xylem hydraulic properties (hydraulic efficiency and safety) trades off with yield and wood anatomical and leaf traits. Our results showed that only three out of 22 investigated ecophysiological traits showed significant genetic differentiations between provenances, namely vessel density (VD), the xylem pressure causing 88% loss of hydraulic conductance and mean leaf size. Depending of the ecophysiological traits measured, genetic differentiation between populations explained 0–14% of total phenotypic variation, while intra-population variability was higher than inter-population variability. Most wood anatomical traits and some foliar traits were additionally related to the climate of provenance origin. The lumen to sapwood area ratio, vessel diameter, theoretical specific conductivity and theoretical leaf-specific conductivity as well as the C:N-ratio increased with climatic aridity at the place of origin while the carbon isotope signature (δ13C) decreased. Contrary to our assumption, none of the wood anatomical traits were related to embolism resistance but were strong determinants of hydraulic efficiency. Although ABI was associated with both VD and δ13C, both hydraulic efficiency and embolism resistance were unrelated, disproving the assumed trade-off between hydraulic efficiency and safety. European beech seems to compensate increasing water stress with growing size mainly by adjusting vessel number and not vessel diameter. In conclusion, European beech has a high potential capacity to cope with climate change due to the high degree of intra-population genetic variability.